The Attitudes of Malaysians Towards Soybean Products - Yeo, P. S (1984)
This study was carried out to determine the..attitudes ofMalaysians towards soybean products. The goal established for this study was: 'How do Malaysians, represented by a random sample of civil employees, jeel towards having more soybean products in their daily diet?" An attitude survey was administered to 23'0 civil employees in Kuala Lumpur. The survey instrument using the Likert Rating Techniques, had 9 statements. Of the 230 copies sent, 211 were returned. The results pertaining to the highlights of the study are discussed. The major findings reveal significant attitudes towards soybean products. Present attitudes and food habits have been identified. The data shows that Malaysians as represented by civil employees have positive attitudes towards soy bean products.